Neuromarketing research in the last five years: A bibliometric analysis - Ahmed H. Alsharif; Nor Zafir Md Salleh; Rohaizat Baharun; Alharthi Rami Hashem E (Cogent Business & Management, 2021)
Neuromarketing (NM) is an application of neuroimaging and physiological tools to record the neural correlates of consumers' behaviour (e.g., decision-making, emotion, attention, and memory) toward marketing stimuli such as brands and advertisements. This study aims to present the current tools employed in the empirical research in the last five years. In this article, we have followed the Preferred Reporting Items for Systematic Review and Meta-analyses (PRISMA) framework and a bibliometric analysis to select empirical and review papers that used NM tools in the last five years. We have extracted and analysed twenty-four documents from the Scopus database to answer our study questions. We found that electroencephalography (EEG) is the most popular neuroimaging tool in neuromarketing research, wherein has been used almost thirteen times. Followed by eye-tracking (ET) and galvanic skin response (GSR) as the most physiological tools, wherein have been applied almost four times for each tool. We hope that this study provides valuable insights into the common NM tools used in marketing research.
Keywords: 650; Neuromarketing; bibliometric analysis; physiological tools; neuroimaging tools